Phylogeny and Biogeography of Carnivorous Plant Family Nepenthaceae With Reference to the Indian Pitcher Plant Nepenthes Khasiana Reveals an Indian Subcontinent Origin of Nepenthes Colonization in South East Asia During the Miocene Epoch - Biswal, Devendra K.; Debnath, Manish; Konhar, Ruchishree; Yanthan, Sureni; Tandon, Pramod (Frontiers in Ecology and Evolution, 2018)
Carnivorous plants popularly known as green predators have long fascinated scientists and general public alike owing to their fascinating trapping mechanisms. Botanical carnivory has evolved independently in five angiosperm orders. In spite of these independent origins, a remarkable convergence of morphological and physiological mechanisms is observed amongst carnivorous plants when it comes to prey capture, assimilation and digestion of animal proteins. The family Nepenthaceae, a monotypic family of the order Caryophyllales exhibits the phenomenon of convergence in morphological traits which makes it difficult to address phylogenetic issues. Using comparative analysis of molecular markers from the nuclear, mitochondrial and plastid DNA the monophyly of the Nepenthaceae family is tested. Sequences from the Indian Nepenthes khasiana, Drosera peltata and Drosera burmannii from the Northeastern state of Meghalaya representing the two important carnivorous families in the order Caryophyllales were determined and analysed using Bayesian and Maximum Likelihood methods. This study examines a genus level analysis by integrating different molecular matrices to existing fossil data on carnivorous plants in a RelTime tree environment for assessing divergence times of the extant Nepenthes species with a focus on its evolutionary origin. Our study has enabled age estimations as well as ancestral area reconstruction to illuminate Nepenthaceae phylogeny and biogeographic history. Divergence time estimates revealed that N. khasiana has an intermediary position between some vestige Western Nepenthes outliers and rest of the taxa by sharing some of the ancient derived traits. Our molecular data speculates Nepenthes evolution to have occurred in the Northern Tethys from the European Eocene (held by fossil pollen records) and a Gondwanaland origin with separation of the Indian plate from Madagascar. Bio-molecular marker data hints at diversification of the family Nepenthaceae from its sister clade Ancistrocladaceae-Dioncophyllaceae in the Early Eocene. These three families had a monophyletic origin of botanical carnivory by getting diversified from Droseraceae in the Late Cretaceous. Colonization of Nepenthes species occurred in South East Asia from an ancient Indian stock (N. khasiana) during 8.16-15 Mya.